2020
DOI: 10.1021/acs.macromol.0c00223
|View full text |Cite
|
Sign up to set email alerts
|

Self-Nucleation Effects on Polymer Crystallization

Abstract: The existence of a "memory" of the previous crystalline state, which survives melting and enhances re-crystallization kinetics by a self-nucleation process, is wellknown in polymer crystallization studies. Despite being extensively investigated, since the early days of polymer crystallization studies, a complete understanding of melt memory effects is still lacking. In particular, the exact constitution of self-nuclei is still under debate. In this perspective, we provide a comprehensive and critical overview … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
270
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(320 citation statements)
references
References 173 publications
15
270
0
Order By: Relevance
“…In [ 26 , 33 , 35 ], a review of these non-trivial problems is given, and general theoretical considerations are outlined showing that near and below the glass transition range the opposite situation can be realized, structural relaxation processes may proceed slowly as compared with crystal nucleation. In such cases, the nucleation kinetics can be significantly affected by structural relaxation processes proceeding in the glass-forming melt as discussed from an experimental point of view in [ 2 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. They result in changes of the state of the liquid in nucleation.…”
Section: The Model: Basic Assumptionsmentioning
confidence: 99%
“…In [ 26 , 33 , 35 ], a review of these non-trivial problems is given, and general theoretical considerations are outlined showing that near and below the glass transition range the opposite situation can be realized, structural relaxation processes may proceed slowly as compared with crystal nucleation. In such cases, the nucleation kinetics can be significantly affected by structural relaxation processes proceeding in the glass-forming melt as discussed from an experimental point of view in [ 2 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. They result in changes of the state of the liquid in nucleation.…”
Section: The Model: Basic Assumptionsmentioning
confidence: 99%
“…For PEO homopolymers, similarly to other macromolecules, the heterogeneous nucleation process has been suggested as the main crystallization mechanism. 22 However, it has been demonstrated that 'melt memory effects' lead to a special case of homogeneous nucleation for PEO homopolymers as well as other macromolecules. 2 The melt memory is a common phenomenon in polymer crystallization where recrystallization of a semicrystalline polymer depends strongly on the existence of the so-called ''melt structure'' of its previous molten state.…”
Section: Introductionmentioning
confidence: 99%
“…2 The melt memory is a common phenomenon in polymer crystallization where recrystallization of a semicrystalline polymer depends strongly on the existence of the so-called ''melt structure'' of its previous molten state. [22][23][24][25] Depending on the temperature of the melt and/or the annealing time in the molten state, the molten state may retain a ''melt structure'' with preserved orientation of the chains. This orientation originates initially from the chain conformations in the crystalline structures or is produced by sticky chain associations of the chains in the melt, due to inter-chain segmental contacts, for example via formation of inter/intramolecular hydrogen bonds or other types of weak forces.…”
Section: Introductionmentioning
confidence: 99%
“…Since the crystallization kinetics and crystal modification of PBSAD are consistent with PBS and the AD units are excluded from the crystalline region, mechanism for the significantly enhanced nucleation capability of PBSAD still remains unclear. According to the work of Zhou’s and Müller’s groups [ 41 , 42 ], PBS could exhibit obvious memory effect that result in a significant increase of nucleation density. The memory effect of chain conformation in melt might be the key factor that promotes the formation of primary nuclei.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the melt memory effect of PBS and PBSAD, the method shown in Figure 8 c is used to partition the nucleation phenomenon of the samples [ 42 ]. For PBSAD-5, there are four specific domains.…”
Section: Resultsmentioning
confidence: 99%